Dynamic Simulation Analysis of the Transmission Mechanism of Rape Matrix Seedling Transplanter - Hu Qingming; Yang Ming; Sun Dandan; Guan Yanqi; Wang Junfeng; Guo Jianhua (Jixie chuandong)
The synchronous belt drive is the main drive form of the driving mechanism of the transplanter. Based on the low stability of the traditional trapezoidal tooth-shaped driving mechanism of the transplanter during seedling separation, it is easy to cause bad tooth skipping and tooth disengaging. A virtual prototype model of the seedling separation device driving mechanism is established by the rigid-flexible coupling multi-body dynamic simulation method to analyze the dynamic characteristics of periodic dynamic load stress variation, transverse vibration, and transmission error of the synchronous belt. The results show that the stress distribution of the straight-toothed synchronous belt (STSB) is more uniform than that of the high torque drive (HTD) and the traditional trapezoidal toothed synchronous belt. The minimum stress value is 59.16 N/mm2, and the minimum amplitude of transverse vibration is 33 mm. The transmission error is small, and the transmission is smooth. It provides reference for dynamic simulation and tooth profile optimization of the driving mechanism of the transplanter.